2008
DOI: 10.1111/j.1365-2958.2008.06498.x
|View full text |Cite
|
Sign up to set email alerts
|

A single aromatic residue in transcriptional repressor protein KorA is critical for cooperativity with its co‐regulator KorB

Abstract: SummaryA central feature of broad host range IncP-1 plasmids is the set of regulatory circuits that tightly control plasmid core functions under steady-state conditions. Cooperativity between KorB and either KorA or TrbA repressor proteins is a key element of these circuits and deletion analysis has implicated the conserved C-terminal domain of KorA and TrbA in this interaction. By NMR we show that KorA and KorB interact directly and identify KorA amino acids that are affected on KorB binding. Studies on mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
19
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 58 publications
5
19
0
Order By: Relevance
“…Substitution W616A led to decreased amounts of NisB that could be co‐purified. Aromatic residues have been reported to play an important role in protein–protein interactions (Halperin et al ., 2004; Bingle et al ., 2008). Thus, it is tempting to speculate that the highly conserved 18F in the leader peptide interacts with NisB through W616.…”
Section: Discussionmentioning
confidence: 99%
“…Substitution W616A led to decreased amounts of NisB that could be co‐purified. Aromatic residues have been reported to play an important role in protein–protein interactions (Halperin et al ., 2004; Bingle et al ., 2008). Thus, it is tempting to speculate that the highly conserved 18F in the leader peptide interacts with NisB through W616.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study also showed that the domains of free KorB act independently, and that the protein exists in a wide range of dynamic conformations [ 21 ]. We have also examined the interaction of KorA with KorB and shown that this is mediated by the C-terminal dimerisation domain of KorA ( Figure 1C ) [ 14 ], as expected from its homology with TrbA [ 15 ].
Figure 1.
…”
Section: Introductionmentioning
confidence: 99%
“…In the case of orf23p, the KorB-exerted repression is also subtle, and we cannot exclude the possibility that this promoter is regulated by another, as-yet-unrecognized protein. However, we could not detect any cooperativity between the primary repressors and KorB RA3 , in contrast to KorB RK2 interacting with two global repressors, KorA and TrbA (3,54,55). Cooperativity between repressor proteins may be important for medium-strength repressors in certain circumstances (4) but not valid for strong and weak repressors interfering with transcription at different levels.…”
Section: Discussionmentioning
confidence: 38%
“…The regulation is achieved by autogenous repressors that produce negative-feedback loops, mediumrange repressors that control particular modules, and globally acting regulators that bind operators scattered along the plasmid molecule to coordinate expression of all modules. Fine-tuning of gene expression is postulated to be achieved by the action of corepressors and their cooperative binding in the promoter regions, which makes the plasmid highly responsive and facilitates its adaptation (1)(2)(3)(4).…”
mentioning
confidence: 99%